Bone variables after a water aerobics program in postmenopausal women undergoing pharmacological treatment - Borba-Pinheiro, Cláudio Joaquim; de Alencar Carvalho, Mauro César Gurgel; Drigo, Alexandre Janotta [UNESP]; da Silva, Nádia Souza Lima; Pernambuco, Carlos Soares; Dantas, Estélio Henrique Martin (Springer Nature, 2012)
Aim: To determine the effects of water aerobics on bone mineral density (BMD) and quality of life (QoL) in postmenopausal women undergoing pharmacological treatment. Methods: Included in the study were 84 women volunteers who were separated into two groups: water aerobics (43 women, age 55.4 ± 6.4 years) and a control group (41 women, age 54.3 ± 4.5 years). Dual X-ray absorptiometry and the Osteoporosis Assessment Questionnaire were used for evaluation. Water aerobics training was scheduled for 12 months. Analysis of variance and the Kruskal-Wallis test were used. Results: No significant intergroup differences were found in the lumbar spine (L2-L4) and femoral neck. However, favorable differences in the trochanter (0.018% difference, p = 0.01) and in QoL (3.4% difference, p = 0.01) were found in the water aerobics group. Conclusion: The results suggest that water aerobics may be beneficial for QoL and BMD in the trochanter in postmenopausal women. However, more recommendation criteria need to be established for BMD. © 2012 Springer-Verlag Italia.
Keywords: Bisphosphonate; Bone density; Physical activity; Quality of life